2010
DOI: 10.1542/peds.2010-1466o
|View full text |Cite
|
Sign up to set email alerts
|

Identifying What Pediatric Residents Are Taught About Children and Youth With Special Health Care Needs and the Medical Home

Abstract: OBJECTIVE:To describe what and how pediatric residents in Massachusetts are taught about children and youth with special health care needs (CYSHCN) and the medical home. PARTICIPANTS AND METHODS:Faculty members and residents at Massachusetts' 5 pediatric residency programs were interviewed to identify current curricula and teaching methods related to care of CYSHCN. In addition, residents were surveyed to quantify these concepts. RESULTS:Thirty-one faculty members and 25 residents were interviewed. Most exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…It is important for future health care providers to learn more about the lives of patients with IDD in the context of their homes and communities [ 25 ]. A single home visit with the family of a child with a disability provides medical residents with insights into the family's perspective on disability, helps them understand these patients outside the hospital context, and increases their appreciation of families as partners in their child's care [ 25 ].…”
Section: Home Visitsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for future health care providers to learn more about the lives of patients with IDD in the context of their homes and communities [ 25 ]. A single home visit with the family of a child with a disability provides medical residents with insights into the family's perspective on disability, helps them understand these patients outside the hospital context, and increases their appreciation of families as partners in their child's care [ 25 ].…”
Section: Home Visitsmentioning
confidence: 99%
“…University of Connecticut medical students participate in a home care and health assessment program as part of their second-year experience. Home and community visits in pediatric residency programs in Massachusetts, teach residents about providing family-centered care for children with special health care needs [ 25 ].…”
Section: Home Visitsmentioning
confidence: 99%
“…5,6 Studies show that less than 25% of pediatricians contact a hospital at the time of a patient's discharge, schedule visits to discuss recommendations of a subspecialist, or contact schools about a child's ongoing medical concerns. 7 Although pediatric trainees and educators believe that medical education for treating CMC should include an understanding of the patients' needs and their families' challenges both within and outside of the medical setting, 8 this type of education has yet to be incorporated into many pediatric training programs. 9 The Institute of Medicine has stated the need to alter the training of the health care workforce to meet the current needs of medically complex patients.…”
Section: What's Newmentioning
confidence: 99%
“…In a study examining what and how Pediatric residents in Massachusetts were taught about children and youth with special health care needs, Pediatric residents and faculty members indicated that the residents would benefit from more formal training opportunities to learn from families about caring for children and youth with special health care needs such as Down syndrome. 24 Faculty recommended that residents need to see the child outside of the hospital to appreciate his or her quality of life. Faculty emphasized the advocacy role for the parents of children and youths with special health care needs.…”
Section: Discrimination Against Children and Families Of Children Witmentioning
confidence: 99%